Specific Aspects of Preliminary Investigation in Certain Foreign Countries (Texas Journal of Multidisciplinary Studies, 2023)
The article analyzes the features of ensuring legality at the initial stage of the investigation, as well as offers suggestions for improving the mechanism of ensuring legality in the activity of the investigator.